Case Report: Early Recognition and Repair of Distal Iatrogenic Ureteral Injury During Laparoscopic Rectal Surgery - Mughni, Abdul; Fuadi, Ahmad Fathi; Daniswara, Nanda (Diponegoro International Medical Journal, 2021)
Background: Ureteral injury is an uncommon complication of the colorectal procedure. The colorectal procedure is the second most common cause of ureteral injury. The laparoscopic approach for colorectal surgery has contributed to the increase of ureteral injury. Delayed diagnosis of the iatrogenic ureteral injury is associated with higher morbidity. However, the early diagnosis of ureteral injury during the operation is difficult. We presented an early recognition and laparoscopic repair of iatrogenic ureteral injury during laparoscopic rectal cancer surgery cases and the strategy for recognizing and managing that injury for the surgeon.Case Presentation: A Male, 34 years old, had an iatrogenic ureteral injury during laparoscopic low anterior resection for rectal cancer. The left distal ureter was transected by an energy device. The diagnosis of ureteral injury was prompt. The repair of the ureter was done endo-laparoscopically. The patient had an uneventful recovery and was discharged on day 6 after surgery.Conclusion: The iatrogenic ureteral injury, although uncommon, is a serious complication of laparoscopic colorectal surgery. Direct visual identification of the distal ureter is mandatory in every rectal surgery. The iatrogenic ureteral injury is not an indication for open conversion when there is an adequate resource to do the endo-laparoscopic ureteral repair.